Smooth to Rough Dissociation in Brucella: The Missing Link to Virulence - Mancilla, Marcos (Frontiers in Cellular and Infection Microbiology, 2016)
Dissociation encompasses changes in a series of phenotypes: colony and cell morphology, inmunological and biochemical reactions and virulence. The concept is generally associated to the in vitro transition between smooth (S) and rough (R) colonies, a phenotypic observation in Gram-negative bacteria commonly made since the beginning of microbiology as a science. It is also well known that the loss of the O-polysaccharide, the most external lipopolysaccharide (LPS) moiety, triggers the change in the colony phenotype. Although dissociation is related to one of the most basic features used to distinguish between species, i.e. colony morphology, and, in the case of pathogens, predict their virulence behaviour, it has been considered a laboratory artifact and thus did not gain further attention. However, recent insights into genetics and pathogenesis of members of Brucella, causative agents of brucellosis, have brought a new outlook on this experimental fact, suggesting that it plays a role beyond the laboratory observations. In this perspective article, the current knowledge on Brucella LPS genetics and its connection with dissociation in the frame of evolution is discussed. Latest reports support the notion that, by means of a better understanding of genetic pathways linked to R phenotype and the biological impact of this intriguing “old” phenomenon, unexpected applications can be achieved.